(untitled) (Research, Society and Development, 2024)
Previous research has shown a high prevalence of patients with intellectual limitations such as Down syndrome, Autism Spectrum Disorder, Turner syndrome, and cerebral palsy. It is a controversial topic because of cognitive impairment, lack of cooperation, and systemic conditions, which have influenced orthodontic treatment to improve function, form, esthetics, and, therefore, health through individual planning regarding behavioral management, interdisciplinary coordination, implementation of appliances, and regular treatment control. Objective: To identify the limitations, behavioral management, and appliances in orthodontic treatment in individuals with cognitive disabilities. Methodology: The databases Medline (PubMed), Science Direct, Virtual Health Library, and Google Scholar were searched using terms obtained from the Medical Subject Headings (MESH) and Descriptors in Health Sciences (DeCS). Results: Thirty-six articles were selected, among which discussions about limitations, behavioral management, and appliances associated with patients with intellectual disabilities were identified. The findings of the review revealed that orthodontic treatment has improved oral health and self-esteem. Conclusion: A combined treatment plan: orthodontics, behavioral management techniques, pharmacological support, and development with a multidisciplinary team are essential to obtain optimal results in form, function, and esthetics.